La sociologie, discipline experte des controverses environnementales ? - Anahita Grisoni; Sophie Némoz (VertigO)
Engaging a discussion between literature and case studies, this article aims to wonder how sociology can take ownership of environmental issues, while social demands for expertise, formulation of standards and inter-disciplinarity have never been stronger. Such expectations are even more specific in the context of environmental controversies. Sociology takes part in the constitution of the field of “environmental sciences” and is therefore, anchored between the two postures of expertise and commitment. The professional experiences of the two authors are at the heart of this reflection. Both in the teaching of sociology and in the participation in research projects, involving other scientific disciplines, knowledge production and sharing can be limited by the partial impossibility to lead a scientific protocol. Is it necessary to give up for all that the idea of inter-disciplinarity between various scientific fields? Is it necessary to put aside the implication of the sociologist in concrete projects, based on an expertise founded on a fundamental research? In the third part of this article, the posture of the committed sociologist - scholarship with commitment (Bourdieu, 2002) – will be revisited not only from the analysis of several situations of research, but also from various experiences in professional structures, in which the sociologist was invited to propose measures serving as basis for action.